2013
DOI: 10.1152/jn.00457.2012
|View full text |Cite
|
Sign up to set email alerts
|

Theories of pain: from specificity to gate control

Abstract: Several theoretical frameworks have been proposed to explain the physiological basis of pain, although none yet completely accounts for all aspects of pain perception. Here, we provide a historical overview of the major contributions, ideas, and competing theories of pain from ancient civilizations to Melzack and Wall's Gate Control Theory of Pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
255
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(274 citation statements)
references
References 51 publications
4
255
0
15
Order By: Relevance
“…There are various major pain theories, including the intensity theory of pain, which postulates that any sensory stimulus with enough intensity can generate pain (2). The peripheral pattern theory suggests that pain is produced by intense stimulation of all skin fiber endings (3), which contradicts the specificity theory, which proposes that there are numerous types of sensory receptors, with each one responding to a specific type of stimuli (4). All of these theories propose that pain is induced by the hyperstimulation of sensory receptors; however, research has suggested that pain may be associated with other sensory stimuli, such as touch (5).…”
Section: Introductionmentioning
confidence: 99%
“…There are various major pain theories, including the intensity theory of pain, which postulates that any sensory stimulus with enough intensity can generate pain (2). The peripheral pattern theory suggests that pain is produced by intense stimulation of all skin fiber endings (3), which contradicts the specificity theory, which proposes that there are numerous types of sensory receptors, with each one responding to a specific type of stimuli (4). All of these theories propose that pain is induced by the hyperstimulation of sensory receptors; however, research has suggested that pain may be associated with other sensory stimuli, such as touch (5).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, stimulation by non-noxious input is able to suppress pain. This explains why pain perception is not felt by the patient during the procedure 20 .…”
Section: Discussion:-mentioning
confidence: 99%
“…The authors describe the patch as a "potent agent for inducing placebo analgesia". It could be that instead of a placebo effect, the patch itself is acting as an analgesic on the basis of the Gate Theory, which can essentially be summarized as the fact that the Aβ fibers inhibit the Aδ and C fibers [20]; in the same way as considered in acupuncture, transcutaneous stimulation or even neuromuscular dressing or kinesiotape [21].…”
Section: Discussionmentioning
confidence: 99%